Behavior of skipjack (Katsuwonus pelamis), yellowfin (Thunnus albacares), and bigeye (T. obsesus) tunas associated with drifting fish aggregating devices (dFADs) in the Indian Ocean, assessed through acoustic telemetry. (26th March 2021) - Govinden, Rodney; Capello, Manuela; Forget, Fabien; Filmalter, John D.; Dagorn, Laurent
Abstract: We investigated the associative behavior of skipjack ( Katsuwonus pelamis ), yellowfin ( Thunnus albacares ), and bigeye ( T. obsesus ) tuna within multi‐species aggregations associated with drifting fish aggregating devices (dFADs) in two different regions of the western Indian Ocean: the Mozambique Channel and the Seychelles, using acoustic telemetry. We documented the residence and absence times of tunas at two temporal scales (coarse and fine scale) and made comparisons between regions. A total of 56 tunas were tagged and released at 7 different dFADs (4 in the Mozambique Channel and 3 in the Seychelles) during four research cruises. We recorded the first observations of skipjack tuna making excursions of more than 24 hours away from dFADs before returning and confirmed findings of other studies showing that yellowfin tuna can make long excursions (4.07 days) before returning to their home dFADs. Combining both studied regions, average residence times were 7.59 days (min 0.03; max 16.49), 6.64 days (min 0.01; max 26.72), and 4.58 days (min 0.09; max 18.33) for bigeye, yellowfin, and skipjack tuna, respectively. Exponential models best fitted the residence times for all three tuna species, indicating time‐independent probabilities of departure from dFADs. For yellowfin tuna, at a coarse temporal scale, no regional differences were observed in the residence times. However, at a fine temporal scale, regional differences were apparent in both residence and absence times. This study provides new information on the associative behavior of tunas at dFADs in the Indian Ocean which is key to improving the science‐based management of dFADs.